Le riforme scolastiche in Tirolo fino al XVIII secolo, con una particolare attenzione all’implementazione del metodo normale - Annemarie Augschöll Blasbichler (Studi sulla Formazione)
The essay illustrates the school reforms in Tyrol up to the 18th century with particular attention to the implementation of the normal method, which is a real challenge from the methodological and cultural point of view in relation to a particular context. The following pages summarize the emergence of the school system and school instruction from the Middle Age to the introduction of the normal method – Normalmethode – which was born in a general context capable of reconstructing the school system in the 17th century. The geographic focus of the study is the German-speaking territory of the County of Tyrol – nowadays the area of the Italian province of Bolzano-Alto Adige and the Austrian region of Tyrol.